Unraveling the physiological and ultrastructural responses of wheat to combat cobalt stress and the protective role of Jania rubens related to antioxidant defense and cellular integrity - Ragab, Gehad A.; Nessem, Afaf A.; Elshobary, Mostafa E.; Henjes, Joachim; Razzaky, Esraa O. (Frontiers in Plant Science, 2025)
Cobalt (Co), while beneficial in trace amounts for biological systems, can severely impact plant growth at elevated levels in contaminated soils. This study investigated the physiological, biochemical and subcellular effects of Co toxicity on wheat (Triticum aestivum L.) and evaluated, for the first time, the protective potential of Jania rubens extract. The algal extract analysis demonstrated its rich content of amino acids, minerals, phytohormones, and fatty acids. Wheat seedlings were subjected to cobalt chloride (150 mM) irrigation, which was previously primed with either water or J. rubens extract. Co stress significantly impaired growth by reducing water content and essential nutrients (K, Mg, and Fe), leading to a 42.42 and 23.8% decrease, respectively, in root and shoot biomasses, a 9% reduction in photosynthetic efficiency, visible chlorosis, and root thickening. Stress exposure also induced oxidative damage, shown by 67.1% increase in hydrogen peroxide and a 170.1% rise in malondialdehyde content, accompanied by membrane leakage and reduced antioxidant enzyme activities. Ultrastructural analysis confirmed morphophysiological and biochemical disruptions at the cellular level. Priming with J. rubens extract significantly alleviated these effects by enhancing nutrient uptake, increasing root and shoot biomasses by 78.94% and 58.33%, respectively, reducing oxidative damage and maintaining cellular homeostasis. It also preserved chloroplast structure, nucleus, and cell wall microtubules, maintaining overall cellular integrity and antioxidant efficiency. Our findings demonstrate that Jania rubens extract offers a promising and novel biogenic strategy for enhancing wheat resilience to cobalt contamination through its nutritional and antioxidant properties.